2007
DOI: 10.1002/cbf.1395
|View full text |Cite
|
Sign up to set email alerts
|

Renal protection by delayed ischaemic preconditioning is associated with inhibition of the inflammatory response and NF‐κB activation

Abstract: Brief and sublethal ischaemia renders an organ tolerant to subsequent prolonged ischaemia, which is called ischaemic preconditioning (IPC). In regard to the beneficial effects and endogenous mechanisms of renal delayed IPC, few data are available. In this study, we aim at determining reno-protective effects of delayed IPC against ischaemia-reperfusion (I/R) injury, and illustrating whether these effects are associated with suppressing inflammation and nuclear factor-kappaB (NF-kappaB) activation. I/R injury wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 32 publications
2
30
1
Order By: Relevance
“…24 The endothelium regulates this latter reaction, since it produces adhesion molecules which enhance PMN attachment and consequent PMN-derived oxidative damage. Although in vitro studies have pointed to reduced ICAM-1 signaling after IPC following an ischemic trigger, 25 and kidney IPC reduced the expressions of ICAM-1 and TNF-alpha and NF-kappaB/ DNA-binding activity, 26 we could not prove similar effects in our model. As ICAM-1 expression can be initiated by proinflammatory cytokines and TNF-alpha, 27 similarly to what was seen with CD11b, reduced TNF release by IPC can make an important contribution to this protection.…”
Section: Discussioncontrasting
confidence: 75%
“…24 The endothelium regulates this latter reaction, since it produces adhesion molecules which enhance PMN attachment and consequent PMN-derived oxidative damage. Although in vitro studies have pointed to reduced ICAM-1 signaling after IPC following an ischemic trigger, 25 and kidney IPC reduced the expressions of ICAM-1 and TNF-alpha and NF-kappaB/ DNA-binding activity, 26 we could not prove similar effects in our model. As ICAM-1 expression can be initiated by proinflammatory cytokines and TNF-alpha, 27 similarly to what was seen with CD11b, reduced TNF release by IPC can make an important contribution to this protection.…”
Section: Discussioncontrasting
confidence: 75%
“…The RK model is widely considered to be a classic model of CKD. Abundant evidence has accumulated indicating that CKD causes oxidative stress [15][16][17] and oxidative stress accelerates the progression of renal injury directly by inducing cytotoxicity and indirectly by promoting inflammation. 1,[16][17][18] Oxidative stress is a known feature of CKD, and its presence is evidenced by the reported elevation of lipid peroxidation products, MDA, and depressed antioxidant capacity.…”
Section: Discussionmentioning
confidence: 99%
“…Details of this technique in our laboratory have been published previously. 15 Positive cells were evaluated in tubulointerstitial areas of the cortex (positive cells/Â200 visual field).…”
Section: Parameters Of Oxidative Stress and Inflammationmentioning
confidence: 99%
“…Previous studies have demonstrated that renal protection by IPC was associated with the inhibition of NF-ĸB activation [22,23]. In this study, we investigated DNA-binding activities of NF-ĸB with EMSA from nuclear protein fractions of the kidneys.…”
Section: Discussionmentioning
confidence: 99%